Effect of autologous stromal vascular fraction (SVF) for diabetes mellitus type-2 - Remelia, Melinda; Novriandina, Shanaz; Karina; Panjaitan, Ani O.; Andriana, Jumaini; Sitohang, John; Batubara, Frisca; Wiyanto, Marwito; Sitompul, Yunita R.M.B (Majalah Kedokteran UKI, 2022)
Autologous Stromal Vascular Fraction (SVF) is one of the alternative therapy for type 2 diabetes that might potentially regenerate pancreatic beta cells. HbA1c levels ≤7% is an efficacious indicator for type 2 diabetes mellitus treatment. The aim of this study is to analyze the effect of autologous SVF therapy on decreasing HbA1c levels of type 2 diabetes patients at Hayandra Clinic in 2016. This study uses observational analytics by obtaining 30 patients' medical records after autologous SVF therapy and analyzing by using paired t-test. The results showed a decrease in HbA1c levels in 24 patients (83.4%), increased HbA1c levels in 4 patients (13.3%), and two patients (3.3%) who had no changes in HbA1c levels after one month got autologous SVF therapy. Based on HbA1c levels as an efficacious indicator, there was an increase in the percentage of type 2 diabetes patients with controlled HbA1c levels from 37% to 47%. The percentage of type 2 diabetes patients with uncontrolled HbA1c levels decreased from 63% to 53%. There was a correlation between autologous SVF therapy and the decrease of HbA1c levels in type 2 diabetes patients (p=0,003). Keywords: Type 2 diabetes; HbA1c levels; Stromal Vascular Fraction